Anti-Müllerian Hormone Signal Transduction involved in Müllerian Duct Regression - Cate, Richard L. (Frontiers in Endocrinology, 2022)
Over seventy years ago, it was proposed that a nonsteroidal hormone made by the fetal testis is required for the complete virilization of the male. At the time the hormone had not yet been identified but was invoked by Alfred Jost to explain why the Müllerian duct, which develops into the female reproductive tract, regresses in the male fetus. That hormone, anti-Müllerian hormone (AMH), has now been extensively characterized along with its specific receptor, AMHR2, and belong to the transforming growth factor- family of protein ligands and receptors involved in growth and differentiation. Much is now known about the downstream events set in motion after AMH engages AMHR2 at the surface of specific Müllerian duct cells and initiates a cascade of molecular interactions that ultimately terminate in the nucleus as activated transcription factors. The signals generated by the AMH signaling pathway are then integrated with signals coming from other pathways and culminate in a complex gene regulatory program that redirects cellular functions and fates and leads to Müllerian duct regression.